Vision after 53 Years of Blindness. (December 2013) - Šikl, Radovan; Šimeček, Michal; Porubanová-Norquist, Michaela; Bezdíček, Ondřej; Kremláček, Jan; Stodůlka, Pavel; Fine, Ione; Ostrovsky, Yuri
Several studies have shown that visual recovery after blindness that occurs early in life is never complete. The current study investigated whether an extremely long period of blindness might also cause a permanent impairment of visual performance, even in a case of adult-onset blindness. We examined KP, a 71-year-old man who underwent a successful sight-restoring operation after 53 years of blindness. A set of psychophysical tests designed to assess KP's face perception, object recognition, and visual space perception abilities were conducted six months and eight months after the surgery. The results demonstrate that regardless of a lengthy period of normal vision and rich pre-accident perceptual experience, KP did not fully integrate this experience, and his visual performance remained greatly compromised. This was particularly evident when the tasks targeted finer levels of perceptual processing. In addition to the decreased robustness of his memory representations, which was hypothesized as the main factor determining visual impairment, other factors that may have affected KP's performance were considered, including compromised visual functions, problems with perceptual organization, deficits in the simultaneous processing of visual information, and reduced cognitive abilities.